Improving Physics Learning Activities and Outcomes Using the Problem-Based Learning Model Assisted by Blooket Media in High School Students - Wahyuni, Nilta; Subiki, Subiki; Ernasari, Ernasari (Universitas Islam Negeri (UIN) Mataram, 2025)
The activities and learning outcomes of physics students in class X of high school are still relatively low due to the lack of student involvement and the use of interesting learning modes. The Problem-Based Learning (PBL) learning model, based on problem solving, if supported by interactive media such as Blooket, will have thepotential to increase student participation and understanding. This study aims to describe the improvement of students' physics learning activities and outcomes using the Problem-Based Learning (PBL) learning model assisted by Blooket media at SMA Negeri 5 Jember. The respondents in this study were students in class X 5 at SMA Negeri 5 Jember. This research uses Classroom Action Research (PTK), which is carried out in two cycles. In this case, each cycle consists of four stages, namely planning, implementation, observation, and reflection. The results of cycle I are used as a benchmark for the implementation of cycle II. Where the implementation of cycle II was carried out to overcome the weaknesses that existed in cycle I. The results of the study showed that the use of the Problem-Based Learning (PBL) learning model assisted by Blooket media experienced an increase in learning outcomes from cycle I to cycle II by 0.53 to 0.73. Then, in the analysis of learning activities in cycle I to cycle II, the percentage increased from the active category to very active, with an average of cycle I of 74.58% and cycle II of 91.67%. Therefore, it can be concluded that the use of the Problem-Based Learning (PBL) learning model assisted by Blooket media can improve students' physics learning activities and outcomes.